Novel insights into the BAP1-inactivated melanocytic tumor - Donati, Michele; Martinek, Petr; Steiner, Petr; Grossmann, Petr; Vanecek, Tomas; Kastnerova, Liubov; Kolm, Isabel; Baneckova, Martina; Donati, Pietro; Kletskaya, Irina; Kalmykova, Antonina; Feit, Josef; et al. (Modern pathology, 2022)
BAP1-inactivated melanocytic tumor (BIMT) is a group of melanocytic neoplasms with epithelioid cell morphology molecularly characterized by the loss of function of BAP1, a tumor suppressor gene located on chromosome 3p21, and a mutually exclusive mitogenic driver mutation, more commonly BRAF. BIMTs can occur as a sporadic lesion or, less commonly, in the setting of an autosomal dominant cancer susceptibility syndrome caused by a BAP1 germline inactivating mutation. Owing to the frequent identification of remnants of a conventional nevus, BIMTs are currently classified within the group of combined melanocytic nevi. "Pure" lesions can also be observed. We studied 50 BIMTs from 36 patients. Most lesions were composed of epithelioid melanocytes of varying size and shapes, resulting extreme cytomorphological heterogeneity. Several distinctive morphological variants of multinucleated/giant cells were identified. Some hitherto underrecognized microscopic features, especially regarding nuclear characteristics included nuclear blebbing, nuclear budding, micronuclei, shadow nuclei, peculiar cytoplasmic projections (ant-bear cells) often containing micronuclei and cell-in-cell structures (entosis). In addition, there were mixed nests of conventional and BAP1-inactivated melanocytes and squeezed remnants of the original nevus. Of the 26 lesions studied, 24 yielded a BRAF mutation, while in the remaining two cases there was a RAF1 fusion. BAP1 biallelic and singe allele mutations were found in 4/22 and 16/24 neoplasms, respectively. In five patients, there was a BAP1 germline mutation. Six novel, previously unreported BAP1 mutations have been identified. BAP1 heterozygous loss was detected in 11/22 lesions. Fluorescence in situ hybridization for copy number changes revealed a related amplification of both RREB1 and MYC genes in one tumor, whereas the remaining 20 lesions studied were negative; no TERT-p mutation was found in 14 studied neoplasms. Tetraploidy was identified in 5/21 BIMTs. Of the 21 patients with available follow-up, only one child had a locoregional lymph node metastasis. Our results support a progression of BIMTs from a conventional BRAF mutated in which the original nevus is gradually replaced by epithelioid BAP1-inactivated melanocytes. Some features suggest more complex underlying pathophysiological events that need to be elucidated.
Keywords: Skin Neoplasms; nádory kůže; protoonkogenní proteiny B-Raf; lidé; hybridizace in situ fluorescenční; Humans; Child; Proto-Oncogene Proteins B-raf; névus; nádorové supresorové proteiny; epiteloidní a vřetenobuněčný névus; Tumor Suppressor Proteins; Nevus, Epithelioid and Spindle Cell; pigmentový névus; Nevus, Pigmented; dítě; Nevus; In Situ Hybridization, Fluorescence; Ubiquitin Thiolesterase; thiolesterasa ubikvitinu